Clinical Outcomes for Radial Artery Versus Saphenous Vein in Coronary Artery Bypass Graft Surgery - Alam, AKM Manzurul; Ahmed, Istiaq; Ahmad, Manzil; Mohashinreza, Md; Hossain, Mamun; Rahman, Mizanur; Sirazi, Saiful Islam (University Heart Journal, 2018)
Aims: The aim this study was to see the clinical outcome of coronary artery bypass grafting (CABG) in patients of coronary artery disease and to compare the patients revascularisedwith left internal mammary artery (LIMA) and radial artery (RA) group with LIMA and reverse saphenous venous group(RSVG) group. Methods:Between March 2011 and November 2015, 200 patients underwent isolated CABG and were randomized in 1:1 fashion to receive either LIMA and RA grafts or LIMA and SVGs.All patients were operated in department of cardiac surgery, National Institute of Cardiovascular Disease (NICVD) and Hospital, Dhaka, Bangladesh and Al Helal Specialized Hospital, Mirpur- 10, Dhaka.Written consent was obtained from all patients prior to the procedure. Patients were followed for 4 years since index surgery for the composite of cardiovascular mortality, non-fatal myocardial infarction and need for repeat myocardial revascularization (either surgical or percutaneous). Data were collected either by phone or during visits. The data were entered into an electronic database (Access, Microsoft) and analyzed using the SPSS 16.0 software (SPSS Inc.). Results: This study reports on our series of 200 patients undergoing isolated, primary CABG using LIMA grafting and the SVG in one group, and RA grafting as the second conduit in the second group. Our data indicate that there is no difference in the long-term clinical outcome between the patients in whom RA or SVG is used as a second conduit, beside LIMA. Conclusion: In this small randomized study our data indicate that there is no difference in the 4 year clinical outcomes in relatively young patients between those having a RA or a saphenous vein graft used as a second conduit, beside LIMA, for surgical myocardial revascularization. University Heart Journal Vol. 13, No. 1, January 2017; 21-25